Case Report : Cervical Cellular Angiofibroma - Mohammad Syarif Hidayatullah; Sharvianty Arifuddin; Nur Rakhmah (Faculty of Medicine, Hasanuddin University., 2022)
Background: Cellular angiofibroma is a rare benign tumor in the distal genitalia introduced by Nucci et al in 1997 that can occur in both women and men with an age range of 46 – 54 years. In women it usually occurs in the vulva and vagina. These tumors are often diagnosed as Bartholin cysts, vulvar cysts, myomas, and unspecified complex tumors. Objective: Report a case of cellular angiofibroma previously diagnosed with cervical myoma Case: A 51-year-old female patient para 5 abortion 0 with complaints of lumps that have been felt to come in and out since 4 months but since 1 week it feels enlarged and cannot be inserted again, and diagnosed as cervical tumor. History of menopause since 1 year ago. The general condition of the patient is good with vital signs within normal limits. On physical examination of the abdomen, there was no tumor mass, tenderness or flux. On inspection, there was a reddish mass coming out of the vaginal introitus with some blackish necrotic appearance. On vaginal examination, a mass with a solid consistency was found with the impression of the cervix with a border of the tumor stalk that was not palpable. In this patient, Total Abdominal Hysterectomy and Bilateral Salpingoophorectomy were performed and the tissue was examined for anatomical pathology with cervical angiofibroma results with non-specific chronic inflammation and atypical complex endometrial gland hyperplasia. Conclusion : Cellular angiofibroma is a rare tumor that usually occur in the vulva and vagina, which is often diagnosed as Bartholin's cyst, vulvar cyst, myoma and unspecified complex tumor. Action in the form of total excision of tumor tissue gives a low recurrence. Keywords : Cervical angiofibroma, cervical tumor